Effectiveness of Electronic Student Worksheet using Problem Based Learning Model on Heat and Heat Transfer Material on the Learning Outcomes of Grade XI Students - Mutiara Puspita; Hidayati Hidayati; Harman Amir; Selma Riyasni (Universitas Negeri Padang in collaboration with Association of Mathematics and Natural Sciences Institution for Education of Teaching Staff Indonesia (AMLI), 2025)
In the current era of digital transformation in education, the quality and variety of learning resources play a crucial role in fostering meaningful learning experiences. However, how student learning outcomes remain a critical issue at MAN Kota Solok, particularly due to the limited variety and lack of attractiveness of the teaching materials currently used. This problem underscores the urgency of developing innovative learning resources that can increase student engagement and conceptual understanding. As a solution, this study implements an Electronic Student Worksheet based on the Problem-Based Learning model, which is designed to make learning more interactive and meaningful. The purpose of this study was to determine the effectiveness of the PBL-based Electronic Student Worksheet in improving student learning outcomes. This research employed a quasi-experimental design with a Posttest-Only Control Design, involving two groups: an experimental group using the PBL-based Electronic Student Worksheet and a control group using the conventional worksheets provided by the school. Data were collected through cognitive posttests and psychomotor assessments during the learning process. The findings revealed that the experimental group achieved higher average scores in both cognitive and psychomotor domains than the control group. Furthermore, hypothesis testing showed that the calculated t-value exceeded the critical t-value, indicating a significant difference between the two groups. These results demonstrate that implementing the PBL-based Electronic Student Worksheet effectively enhances student learning outcomes. This study contributes to the development of innovative digital learning resources that not only foster active student participation but also promote deeper conceptual understanding.